Potential alkali-reactivity of granite aggregates in the Bukit Lagong area, Selangor, Peninsular Malaysia - Ng, Tham Fatt; John K. Raj,; Azman A. Ghani, (Universiti Kebangsaan Malaysia, 2013)
The Bukit Lagong area is the most important aggregate supply centre in Selangor. Geological studies were carried out in four quarries in the Bukit Lagong area and samples were subjected to petrographic examination and accelerated expansion tests to assess the potential alkali-aggregate reactivity of granite aggregates. The granitic rocks comprise mainly of coarse grained megacrystic granite, minor medium grained megacrystic granite and microgranite. Petrographic examination showed that the primary minerals in these undeformed granitic rocks are not alkali reactive. Faulting and related alteration and mineralization have produced potentially alkali reactive minerals including microcrystalline and strained quartz and fine phyllosilicates. Marginally deleterious and deleterious expansion is shown by the accelerated mortar bar tests. Although alkali reactive rocks are present in some quarries in Bukit Lagong, their volume is small. When blended with the undeformed granitic rocks, the aggregates produced are not expected to cause alkali-aggregate reaction in concrete.